Tuberculosis preventive treatment: the next chapter of tuberculosis elimination in India. Issue 5 (8th October 2018) - Moonan, Patrick K; Nair, Sreenivas A; Agarwal, Reshu; Chadha, Vineet K; Dewan, Puneet K; Gupta, Umesh D; Ho, Christine S; Holtz, Timothy H; Kumar, Ajay M; Kumar, Nishant; Kumar, Prahlad; Maloney, Susan A; et al.
Abstract : The End TB Strategy envisions a world free of tuberculosis—zero deaths, disease and suffering due to tuberculosis by 2035. This requires reducing the global tuberculosis incidence from >1250 cases per million people to <100 cases per million people within the next two decades. Expanding testing and treatment of tuberculosis infection is critical to achieving this goal. In high-burden countries, like India, the implementation of tuberculosis preventive treatment (TPT) remains a low priority. In this analysis article, we explore potential challenges and solutions of implementing TPT in India. The next chapter in tuberculosis elimination in India will require cost-effective and sustainable interventions aimed at tuberculosis infection. This will require constant innovation, locally driven solutions to address the diverse and dynamic tuberculosis epidemiology and persistent programme monitoring and evaluation. As new tools, regimens and approaches emerge, midcourse adjustments to policy and practice must be adopted. The development and implementation of new tools and strategies will call for close collaboration between local, national and international partners—both public and private—national health authorities, non-governmental organisations, research community and the diagnostic and pharmaceutical industry. Leading by example, India can contribute to global knowledge through operational research and programmatic implementation for combating tuberculosis infection.